MENINGKATKAN PARTISIPASI KAUM BAPAK DALAM KOOR LITURGI DI KUB SANTO YOHANES PAULUS II PAROKI ST. MATIAS RASUL TOFA, KUPANG - Tamelab, Petrus (Pastoralia Jurnal Penelitian Dosen, 2021)
The Second Vatican Council opened the veil of darkness in the Catholic church. The birth of the Second Vatican Council was the right moment for the Catholic Church to open itself to others of different religions, ethnicities and races. One of the things experienced in the Catholic Church is that it requires people to take active part in the eucharist of salvation. In this regard, all believers involve themselves as much as possible in various Church activities at KUB, in particular liturgical choir training. In this study, I focus my attention on the phenomenon that occurred at KUB Santu Yohanes Paul II Oebufu, namely the minimal participation of fathers in the liturgical choir. When investigated by the informants who provided information, it was found that there were various reasons. Some say that ego is dominant, while others say that mental awareness as Catholics is still minimal. It is necessary to realize that fathers should be role models in the family's faith life. So when the father is involved in various Church activities, it is certain that family members will emulate that attitude. However, if the opposite happens, that the fathers are passive in activities at KUB, then family members, especially children, will imitate their father's attitude. The Latin proverb says: "qui bene cantat bis orat" (who sings well he prays twice). The meaning of this proverb is that by singing well you are actually expressing your intentions and gratitude to God.